THE EFFECT OF e-WOM AND BRAND LOVE ON THE PURCHASING DECISIONS IN ONLINE SHOPPING - Dwi Rahayu (Jurnal Ilmiah Publipreneur, 2020)
The objectives of this research are: to analyze the effect of e-WOM on brand love, to analyze the effect of e-WOM on purchasing decisions in online shopping, to analyze the effect of brand love on purchasing decisions in online shopping. This research used quantitative methods, with a total sample of 243 online shopping in the Jabodetabek area. The research used online survey methods in the form of questionnaires. The sampling technique used purposive sampling. The scaling technique of the study applied Likert scale which produces measurements at intervals; scale 1 for strongly disagree statements and scale 5 for strongly agree statements. The data analysis used SEM (Structural Equation Modeling).The findings showed that there is a positive effect of e-WOM variable on brand love variable with a t-count value of 7.01 with an estimate of 0.43. The e-WOM variable has a positive effect on purchase decision with t-count value of 7.08 with an estimate of 0.47. Brand love is the last variable that has a positive effect on purchasing decisions with a t-count value of 6.92 with an estimate of 0.35.